Strengthening Village Community Governance Through the Preparation of Awig-Awig - Karyati, Sri; Ulum, Hafizatul; Kamil, Muhammad Ikhsan; Aswadi, Khairul; Zain, Irma Istihara; Kusuma, Jauhari Dewi (Faculty of Law Pattimura University, 2025)
Introduction: One of the important aspects in village institutional development is the existence of rules that are mutually agreed upon by the community as guidelines in the implementation of village government. Laws and regulations at the village level, namely village regulations, are determined according to the legal needs of the village. However, in the implementation there are also rules born from local values and local culture, especially in Pujut village, East Praya district, Central Lombok regency, there are awig-awig who have an important role in maintaining social order, resolving conflicts, and strengthening the sense of togetherness and identity of the village community. So it is necessary to strengthen village community governance through assistance in the preparation of awig-awig in Mujur village.Purposes of The Devotion: The main purpose of this activity is to strengthen the capacity of the Mujur village government apparatus, Mujur village Bamusdes and the people of Mujur Village in preparing a draft regulation on village awig-awig as part of the village governance system. Method of The Devotion: The service method is carried out with assistance in the preparation of awig-awig in Mujur Village involving village government officials, village consultative bodies, heads of neighborhoods, traditional leaders, and representatives of the village community, so that the results reflect the needs and aspirations of the people of Mujur village.Results Main Findings of the Devotion: The implementation of this community service activity contributes to the partners, namely the understanding of the formation of village awigs stipulated in the form of a draft village regulation on Mujur village awigs, prepared by the village government with the participation of the Mujur village community.